CAREER STUDENT INTEREST PREFERENCES ON SHARIA FINANCIAL SERVICES - antoni, syafrul - (Pusat P2M Politeknik Negeri Batam, 2023)
ABSTRAKThe study aims to determine students' interest in a career in Islamic financial services, as well as what factors influence students to be interested in Islamic financial services. The number of samples in this study were 90 respondents with the sampling method using random sampling method. Data collection was carried out through a questionnaire. Data analysis uses the help of the IBM SPSS Statistics application. The results showed that religiosity had no effect on students' interest in having a career in Islamic financial services while subjective norms had an effect on students' interest, and behavioral control had no effect on students' interest in the Islamic economics and business faculties of Iain Kerinci in choosing a career in Islamic financial services. Keywords: Religiosity, subjective norms, behavioral control, interest in a career in Islamic financial services.